Cultures and crises : understanding risk and resolution - Douglas, Mary, 1921-2007; Fardon, Richard (Los Angeles : : SAGE, 2013)
"Written in the last two decades of her life, Cultures and Crises finds Mary Douglas developing analyses of critical conditions facing contemporary societies, sometimes in the company of distinguished co-authors across the whole gamut of social sciences. The essays focus on the collaborative development of 'cultural theory' from the 'grid and group' analysis of the 1970s through to its application and elaboration in her later thought. The material covers questions of culture and institutions, the challenges to culture posed by climate change and the nature of risk in culture. What emerges is the most complete picture of Mary Douglas's cultural theory that is currently available to us. The book will add to the legions of Douglas's readers across the disciplinary divisions of the social sciences."--Publisher's website.
Introduction: How Cultures Precipitate Risk and Resolution / Richard Fardon. -- Part 1: Cultural theory. The Language of Emotions in the Social Sciences ; Emotion and Culture in Theories of Justice ; Institutions: Problems of Theory ; Four Cultures: The Evolution of a Parsimonious Model. -- Part 2: Culture and climate. Human Needs and Wants / Des Gasper, Steven Ney and Michael Thompson ; Is Time Running out? The Case of Global Warming / Michael Thompson and Marco Verweij ; Clumsy Solutions for a Complex World: The Case of Climate Change / Marco Verweij et al ; An Aesthetic View of the Relation between Culture and Nature ; Postscript: The Future of Clumsiness / Christoph Engel, Michael Thompson and Marco Verweij. -- Part 3: Institutionalized risks. The Risks of the Risk Officer ; Dangerization and the End of Deviance: The Institutional Environment / Michalis Lianos ; Postscript / Michalis Lianos ; Terrorism: A Positive Feedback Game / Gerald Mars ; Postscript / Gerald Mars ; Being Fair to Hierarchists ; Traditional Culture: Let's Hear no More about It ; Endpiece: The Selfish Giant / Oscar Wilde.
Errata slip inserted.
Includes bibliographical references and index.
Keywords: Culture; Risk -- Sociological aspects; Human beings -- Effect of environment on; Human ecology